Pengembangan Edukasi Teknologi Melalui Game Rohani Kepada Anak-Anak Kristen Masa Kini di GKLI Sipoholon - Agustinus Gulo; Johannes GB Panjaitan; Remita Nian Permata Zendrato; Eni Marlina Sihombing; Yersi Hotmauli Berutu; Elsina Sihombing (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2023)
The purpose of this study was to develop children's ability to use technology through spiritual games. The research method used in this study is a qualitative approach method. Data collection using observation techniques and direct interviews with children and Sunday school teachers at GKLI Sipoholon. The results showed that the use of spiritual games has the potential to increase children's understanding of religious teachings and morality. The importance of developing spiritual education in the digital era demands creativity and innovation in providing learning to children. In an era of ever-evolving technology, education in the church environment requires an innovative approach. Spiritual games are defined as interactive game applications specifically designed to provide religious and moral learning experiences. Spiritual games are an interesting bridge to the world of Christian children. Through the development of technological media, especially spiritual games. Thus, the development of technology education through spiritual games at GKLI Sipoholon is a progressive step in educating and guiding Christian children today, in line with the mission of spiritual formation of the church.